Pyrenyl‐Based Aggregation‐Induced Emission Luminogen for Highly Sensitive and Selective Detection of 2, 4, 6‐Trinitrotoluene in Water. Issue 43 (18th November 2021) - Hao, Hongmin; Ye, Zijian; Dai, Hui; Liu, Cong; Yi, Aihua; Xu, Bingjia; Shi, Guang; Su, Shichen; Azad, Fahad; Chi, Zhenguo
Abstract: Trace detection of nitroaromatic explosives in aqueous solution is important for environmental pollution evaluation and terrorist prevention. Here, a new pyrenyl‐based aggregation‐induced emission (AIE) fluorochrome (CPPyV) with desirable fluorescent performance was synthesized and applied to detect 2, 4, 6‐trinitrotoluene (TNT) in water. The fluorescence of CPPyV can be selectivity and efficiently quenched by TNT. The Stern‐Volmer constant (KSV ) of CPPyV for TNT was determined to be 6.2×10 5 M −1, with a low detection limit of 4 nM. Notably, CPPyV could be used for TNT determinations in real water samples and also developed as a fluorescent paper sensor which could efficiently detect TNT by naked‐eye when the TNT concentration was 1.0×10 −8 M. The quenching process was dynamic quenching mechanism and the theoretical calculations revealed that photoin‐duced electron transfer (PET) from excited CPPyV to electron deficient TNT was the main reason for fluorescence quenching. The excellent detection performance of CPPyV yielded it a promising sensor material for actual field applications. Abstract : A small pyrenyl‐based AIE fluorochrome (CPPyV) was reported, which was synthesized via a simple route. CPPyV had the advantages of high selectivity and sensitivity in the detection of TNT, with a low detection limit of 4 nM. Notably, CPPyV could be used for TNT determinations in real water samples and also developed as a fluorescent paper sensor which could efficiently detect TNT by naked‐eye when the TNT concentration was 1.0×10 −8 M.